Fiscal Stimulus Impact on Firms' Profitability During the Global Financial Crisis - Correa-Caro, Carolina (IMF Working Papers; Working Paper ;, 2018)
Using financial statement data from the Thomson Reuter's Worldscope database for 22,333 non-financial firms in 52 advanced and emerging economies, this paper examines how fiscal stimulus (i.e., changes in structural deficit) interacted with sectoral business cycle sensitivity affected corporate profitability during the recovery period of the global financial crisis (GFC). Using cross-sectional analyses, our findings indicate that corporate profitability improved significantly after the GFC fiscal stimulus, especially in manufacturing, utilities and retail sectors. Firm size and leverage are also found to be significant in explaining changes in corporate profitability.